Precocious Preclinical Cardiovascular Sonographic Markers in Metabolically Healthy and Unhealthy Childhood Obesity - Corica, Domenico; Oreto, Lilia; Pepe, Giorgia; Calabrò, Maria Pia; Longobardo, Luca; Morabito, Letteria; Pajno, Giovanni Battista; Alibrandi, Angela; Aversa, Tommaso; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2020)
Background: Childhood obesity is related to a wide spectrum of cardiovascular and metabolic comorbidities. Objectives: (1) To identify precocious, preclinical, cardiovascular sonographic modifications, in a cohort of overweight (OW) and obese (OB) children and adolescents compared to lean controls; (2) to investigate the association between clinical and metabolic variables and cardiovascular sonographic parameters; (3) to evaluate their relation with two different phenotypes of obesity: metabolically healthy obesity (MHO) and metabolically unhealthy obesity (MUO). Materials and Methods: Fifty-nine OW and OB children and adolescents (9.8 ± 2.9 years) and 20 matched lean controls underwent anthropometric, biochemical, echocardiography assessment, and sonographic evaluation of carotid artery and ascending aorta (AA). OW and OB subjects were divided in MHO and MUO, according to the Camhi et al. definition. Results: OW and OB children showed significantly higher left ventricular (LV) dimensions and mass, carotid artery intima–media thickness (CIMT), carotid stiffness [β-index, pulse wave velocity (PWV)], significantly lower mitral peak early (E) and late (A) velocity ratio (E/A ratio), and significantly impaired global longitudinal strain (GLS) compared to controls. BMI SD and HOMA-IR were positively significantly related to LV dimensions, LA volume and epicardial adipose tissue (EAT), and negative to E/A ratio. Waist circumference (WC) was positively correlated to LV dimensions, LA volume, CIMT, PWV, AA diameter, and EAT. Furthermore, WC was a strong predictor of LV dimensions, LA volume and strain, AA stiffness and diameter; BMI SD was significantly associated with EAT, LVM index, and E/A ratio; HOMA-IR and triglycerides were significant predictors of GLS. MUO patients showed higher BMI SD (p = 0.02), WC (p = 0.001), WHtR (p = 0.001), HOMA-IR (p = 0.004), triglycerides (p = 0.01), SBP (p = 0.001), as well as LV dimensions, EAT (p = 0.03), CIMT (p = 0.01), AA diameter (p = 0.02), β-index (p = 0.03) and PWV (p = 0.002), AA stiffness (p = 0.006), and significantly impaired GLS (p = 0.042) compared to MHO. Conclusions: Severity of overweight, abdominal obesity, insulin resistance, and MUO phenotype negatively affect cardiovascular remodeling and subclinical myocardial dysfunction in OW and OB children. MUO phenotype is likely to increase the risk of developing cardiometabolic complications since the pediatric age. Distinction between MHO and MUO phenotypes might be useful in planning a personalized follow-up approach in obese children.